2019
DOI: 10.1002/tox.22731
|View full text |Cite
|
Sign up to set email alerts
|

Nickel‐induced VEGF expression via regulation of Akt, ERK1/2, NFκB, and AMPK pathways in H460 cells

Abstract: Prospective cohort studies have indicated that a highly nickel-polluted environment may severely affect human health, resulting in such conditions as respiratory tract cancers. Such exposure can trigger vascular endothelial growth factor (VEGF) expression. However, the signal transduction pathways leading to VEGF induction by nickel compounds are not well understood.This study revealed the occurrence of VEGF induction in human non-small-cell lung cancer H460 cells exposed to NiCl 2 . Moreover, exposing H460 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 33 publications
2
19
0
Order By: Relevance
“…Indeed, ERK/MAPK signaling was predicted in the IPA analysis for Ni NPs and NiCl 2 in our study ( Figure 5). Previous studies have also suggested a role for PI3K/Akt and ERK signaling followed by Vascular Endothelial Growth Factor (VEGF) expression as a response to Ni [9,28,29]. We also recently reported the secretion of VEGF in THP-1-derived macrophages following exposure to Ni and NiO NPs [30] and, in the present study on BEAS-2B cells, increased transcription of VEGFA was observed for NiCl 2 (see Figure 5).…”
Section: Discussionsupporting
confidence: 80%
“…Indeed, ERK/MAPK signaling was predicted in the IPA analysis for Ni NPs and NiCl 2 in our study ( Figure 5). Previous studies have also suggested a role for PI3K/Akt and ERK signaling followed by Vascular Endothelial Growth Factor (VEGF) expression as a response to Ni [9,28,29]. We also recently reported the secretion of VEGF in THP-1-derived macrophages following exposure to Ni and NiO NPs [30] and, in the present study on BEAS-2B cells, increased transcription of VEGFA was observed for NiCl 2 (see Figure 5).…”
Section: Discussionsupporting
confidence: 80%
“…ANGPTL4 has been recognized as an indicator of whether breast cancer will metastasise to the lung [29], and other studies have indicated that TGF-β primes breast tumours for the seeding of lung metastasis through ANGPTL4 by modulating endothelial integrity to mediate lung metastasis seeding [11]. In our recent investigation, NiCl 2 increased the level of integrin beta 3 (ITGB3) through TGF-β signalling [27]. In addition, Zhu et al indicated that tumour-derived ANGPTL4 interacts with integrins to elevate the O2 − /H 2 O 2 ratio, thus stimulating tumour development [30].…”
Section: Discussionmentioning
confidence: 74%
“…It has been demonstrated that NiCl 2 has high invasive potential, which promotes angiogenesis and the acquisition of a persistent mesenchymal phenotype in lung cancer cells, via different pathways [26][27][28]. ANGPTL4 has been recognized as an indicator of whether breast cancer will metastasise to the lung [29], and other studies have indicated that TGF-β primes breast tumours for the seeding of lung metastasis through ANGPTL4 by modulating endothelial integrity to mediate lung metastasis seeding [11].…”
Section: Discussionmentioning
confidence: 99%
“…Recent reviewers found that VEGF could induce the activation of Akt, ERK1/2, NF-κB and AMPK pathways in H460 cells ( 19 ). These reviewers proposed VEGF binds to its receptor (VEGFR) to further induce the activation of the downstream signals in tumor endothelial cells, including the extracellular regulated protein kinases (ERK), NF-κB and threonine protein kinase (Akt)/mammalian target of rapamycin (mTOR) pathways.…”
Section: Discussionmentioning
confidence: 99%